A composite iron phosphate and its preparation method and application
By using tin dioxide and ultraviolet light irradiation technology of hollow nanofiber structures in the preparation process of iron phosphate, strong oxidation free radicals are generated to oxidize divalent iron to form tin dioxide composite iron phosphate material, solving the problems of low efficiency and poor performance of iron phosphate preparation in the prior art, and significantly improving the electrical performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202380011850.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
The prior art has low efficiency when preparing iron phosphate, and the obtained iron phosphate has poor performance, which cannot effectively improve the electrical performance of lithium-ion batteries.
Tin dioxide with hollow nanofiber structure is used to generate free radicals with strong oxidation capacity through ultraviolet light irradiation, divalent iron is oxidized to trivalent iron, and tin dioxide composite iron phosphate material is formed by adjusting pH.
The electrical performance of lithium batteries has been improved, and the 0.1C discharge capacity of the produced battery can reach more than 157.5mAh/g, the 1C discharge capacity can reach more than 146.5mAh/g, and the discharge capacity can reach more than 143.7mAh/g after 100 cycles of 1C, and the cycle retention rate can reach more than 98.1%.
Smart Images

Figure CN117957188B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials and relates to a composite iron phosphate and a preparation method and application thereof. Background Art
[0002] As the industrial revolution continues to develop and sustainable green energy is developed, lithium-ion batteries (LIBs), as an efficient energy storage device, have become well-known and widely used in various fields. Among them, lithium iron phosphate (LiFePO4) lithium-ion batteries have attracted much attention due to their excellent performance. They not only have excellent cycle performance and high safety, but more importantly, their raw materials are widely available and low in cost. The common method in industry is to use iron phosphate and lithium source as raw materials, and prepare lithium iron phosphate by reaction sintering under high temperature heating. Therefore, the iron phosphate as a raw material has an important influence on the performance of lithium iron phosphate positive electrode materials in terms of structure, morphology and properties.
[0003] The main method for preparing iron phosphate is the co-precipitation method, which usually uses a cheap and easily available divalent iron source as a raw material, adds hydrogen peroxide to oxidize the divalent iron into trivalent iron, and then reacts with a phosphorus source to form iron phosphate by co-precipitation. This method must consume a large amount of oxidant, which increases the preparation cost to a certain extent.
[0004] CN109305663A discloses a battery-grade anhydrous ferric phosphate and a preparation method thereof. In the process of preparing the ferric phosphate, air is used as an oxidant without consuming additional chemical oxidants, thus saving preparation costs. However, the air oxidation efficiency is relatively low.
[0005] CN114644327A discloses a method for preparing iron phosphate and its application, wherein the iron phosphate is directly prepared by reacting an iron source with phosphoric acid under certain conditions such as low temperature, and then oxidizing the filtrate with hydrogen peroxide.
[0006] The above scheme adopts an oxidation method to prepare iron phosphate, but the efficiency is low, and the performance of the prepared iron phosphate is poor, and it cannot effectively improve the electrical performance of the battery. Summary of the invention
[0007] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.
[0008] The purpose of the present disclosure is to provide a composite iron phosphate and a preparation method and application thereof. The present disclosure first introduces tin dioxide with a hollow nanofiber structure, irradiates the tin dioxide with ultraviolet light to generate free radicals with strong oxidizing ability on its surface, oxidizes divalent iron into trivalent iron, adjusts the pH to co-precipitate to form a tin dioxide composite iron phosphate material, and at the same time, the introduction of tin dioxide helps to improve the electrical properties of lithium batteries.
[0009] To achieve this purpose, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present disclosure provides a method for preparing a composite iron phosphate, the preparation method comprising the following steps:
[0011] (1) mixing a tin source and a template agent with a first solvent, heating and stirring to obtain a spinning solution, and sintering after electrospinning to obtain hollow nanofiber tin dioxide;
[0012] (2) The hollow nanofiber tin dioxide, ferrous source and phosphorus source are mixed with a second solvent, subjected to light treatment while adjusting the pH, and then aged and calcined to obtain the composite iron phosphate.
[0013] The present invention discloses a hollow nanofiber tin oxide prepared by electrospinning technology. Since the hollow structure has a relatively large surface free energy, it can adsorb ions and attach to its surface. As a seed, it can accelerate the precipitation of primary particles of iron phosphate. During the reaction, light is irradiated. Tin dioxide acts as a photocatalyst and stimulates the separation of electron-hole pairs under light, forming hydroxyl radicals (·OH) and superoxide radicals (·O2 - ), directly oxidizes the divalent iron into trivalent iron without adding any additional oxidant, and forms a composite of tin dioxide / ferric phosphate.
[0014] In one embodiment, the tin source in step (1) includes any one of stannous chloride, tin tetrachloride, tin nitrate or tin sulfate, or a combination of at least two thereof.
[0015] In one embodiment, the templating agent comprises polyvinyl pyrrolidone and / or polyacrylonitrile.
[0016] In one embodiment, the mass ratio of the tin source to the template is (0.95-1.05):1, for example: 0.95:1, 0.98:1, 1:1, 1.02:1 or 1.05:1, etc.
[0017] The present invention can prepare hollow nanofiber tin dioxide with suitable particle size and stable structure by controlling the mass ratio of the tin source and the template agent within the above range.
[0018] In one embodiment, the first solvent comprises ethanol and DMF.
[0019] In one embodiment, the mass ratio of ethanol to DMF is (1-3):1, for example: 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, etc.
[0020] The present invention uses a mixed solution of ethanol and DMF as a solvent. By adjusting the addition ratio of raw materials, the composition and ratio of the solvent, etc., a spinning solution with a suitable composition can be obtained. In the subsequent electrospinning process, the spinning solution can obtain a structurally stable hollow nanofiber tin dioxide.
[0021] In one embodiment, the temperature of the heating and stirring is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C.
[0022] In one embodiment, the heating and stirring time is 12 to 48 hours, for example: 12 hours, 16 hours, 24 hours, 32 hours or 48 hours.
[0023] In one embodiment, the receiving distance of the electrospinning treatment in step (1) is 12 to 25 cm, for example, 12 cm, 15 cm, 18 cm, 20 cm or 25 cm.
[0024] In one embodiment, the voltage of the electrospinning process is 10-18 kV, for example, 10 kV, 12 kV, 14 kV, 16 kV or 18 kV.
[0025] In one embodiment, the electrospinning treatment rate is 0.1 to 2 mL / h, for example, 0.1 mL / h, 0.5 mL / h, 1 mL / h, 1.5 mL / h or 2 mL / h.
[0026] In one embodiment, the heating rate of the sintering is 0.5 to 3°C / min, for example, 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min or 3°C / min.
[0027] In one embodiment, the sintering temperature is 550-650°C, for example, 550°C, 580°C, 600°C, 620°C or 650°C.
[0028] In one embodiment, the sintering time is 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours.
[0029] The present invention prepares hollow nanofiber tin dioxide by controlling the fiber-forming process, thermal decomposition during calcination, and crystal nucleation growth process.
[0030] In one embodiment, the ferrous source in step (2) includes any one of ferrous sulfate, ferrous nitrate or ferrous chloride, or a combination of at least two thereof.
[0031] In one embodiment, the phosphorus source includes any one of phosphoric acid, ammonium hydrogen phosphate, sodium phosphate or diammonium dihydrogen phosphate, or a combination of at least two thereof.
[0032] In one embodiment, the molar ratio of tin in the hollow nanofiber tin dioxide, iron in the ferrous source and phosphorus in the phosphorus source is (0.03-0.1):(0.98-1):1, for example: 0.03:0.98:1, 0.05:0.985:1, 0.06:0.98:1, 0.08:0.99:1 or 0.1:1:1, etc.
[0033] During the preparation process of the composite lithium iron phosphate positive electrode material disclosed in the present invention, the amount of tin added will affect its performance. The molar ratio of tin element in tin dioxide to iron element in ferrous source is controlled at (0.03-0.1):1, and the composite lithium iron phosphate with better performance is obtained. If the amount of tin added is too large, the proportion in iron phosphate is too high, and then it also occupies a non-negligible part in the subsequent synthesis of lithium iron phosphate, affecting the proportion of active substances in the positive electrode material; if the amount of tin added is too small, the oxidation of divalent iron is incomplete, and trivalent iron and divalent iron coexist in the solution. When generating iron phosphate, the divalent iron will be brought into the iron phosphate and co-precipitated together. The obtained iron phosphate contains impurity ions, which affects the material performance and has not fully utilized the iron source.
[0034] In one embodiment, the second solvent comprises deionized water.
[0035] In one embodiment, the light source of the illumination in step (2) includes ultraviolet light.
[0036] The present invention uses ultraviolet light to better stimulate the photocatalytic effect of tin dioxide.
[0037] In one embodiment, the illumination time is 1 to 3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0038] During the preparation process of the composite lithium iron phosphate positive electrode material disclosed in the present invention, the illumination time will affect its performance. When the illumination time is controlled within 1 to 3 hours, the composite lithium iron phosphate has better performance. If the illumination time is too short, sufficient free radicals cannot be generated, which will lead to incomplete oxidation of divalent iron.
[0039] The reaction equation for the illumination described in the present disclosure is as follows:
[0040] SnO2+hv→h vb + +e cb -
[0041] h vb + +H2O→·OH+H +
[0042] h vb ++OH - → OH
[0043] e cb - +O2 → ·O2 -
[0044] Fe 2+ +·OH→Fe 3+ +OH -
[0045] Fe 2+ +·O2 - →Fe 3+ +O2.
[0046] In one embodiment, the method of adjusting the pH comprises adding an alkaline substance.
[0047] In one embodiment, the pH is 1.4 to 2.2, for example: 1.4, 1.6, 1.8, 2, 2.2, etc.
[0048] The present invention can produce solid precipitation by adjusting the pH, and then carry out the subsequent process.
[0049] In one embodiment, the aging temperature in step (2) is 65-95°C, for example, 65°C, 70°C, 75°C, 80°C or 95°C.
[0050] In one embodiment, the aging time is 3 to 12 hours, for example, 3 hours, 5 hours, 8 hours, 10 hours or 12 hours.
[0051] The present invention can help generate iron phosphate crystals through aging, thereby improving the structural stability of the material.
[0052] In one embodiment, the aging is followed by filtering, washing and drying.
[0053] In one embodiment, the washing detergent comprises deionized water.
[0054] In one embodiment, the washing is performed 3 to 5 times, for example, 3, 4 or 5 times.
[0055] In one embodiment, the calcination temperature is 500-750°C, for example, 500°C, 550°C, 600°C, 650°C or 750°C.
[0056] In the preparation process of the composite lithium iron phosphate positive electrode material disclosed in the present invention, the temperature of calcination after illumination will affect its performance. The temperature of calcination after illumination is controlled at 500-750°C to obtain a composite lithium iron phosphate with better performance. If the temperature of calcination after illumination is too high, tin dioxide will affect the lattice characteristics of iron phosphate. If the temperature of calcination after illumination is too low, tin dioxide and iron phosphate will not be well composited, the dehydration of iron phosphate is incomplete, and some impurities have not been completely removed.
[0057] In one embodiment, the calcination time is 4 to 8 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.
[0058] In a second aspect, the present disclosure provides a composite iron phosphate, which is prepared by the method described in the first aspect.
[0059] In a third aspect, the present disclosure provides a composite lithium iron phosphate positive electrode material, wherein the composite lithium iron phosphate positive electrode material is prepared by mixing the composite iron phosphate as described in the second aspect with a lithium source and a carbon source and calcining the mixture.
[0060] In one embodiment, the lithium source includes any one of lithium hydroxide, lithium carbonate or lithium acetate, or a combination of at least two thereof.
[0061] In one embodiment, the carbon source includes any one of glucose, sucrose, phenolic resin, starch, dextrin, citric acid, oxalic acid, cellulose or vitamins, or a combination of at least two thereof.
[0062] In one embodiment, the molar ratio of the iron element in the composite iron phosphate to the lithium element in the lithium source is 1:(1-1.03), for example: 1:1, 1:1.01, 1:1.015, 1:1.02 or 1:1.03, etc.
[0063] In one embodiment, the mass of the carbon source is 3% to 15% of the total mass of the composite iron phosphate and the lithium source, for example, 3%, 5%, 8%, 10% or 15%.
[0064] In one embodiment, the calcination atmosphere in step (3) comprises nitrogen and / or argon.
[0065] In one embodiment, the calcination includes one-step calcination and two-step calcination.
[0066] The present invention discloses a composite lithium iron phosphate positive electrode material with good capacity performance and cycle performance through two-step calcination without affecting the stability of the material structure.
[0067] In one embodiment, the temperature of the one-step calcination is 400-500°C, for example, 400°C, 420°C, 450°C, 480°C or 500°C.
[0068] In one embodiment, the one-step calcination time is 0.5 to 2 h, for example, 0.5 h, 0.8 h, 1 h, 1.5 h or 2 h.
[0069] In one embodiment, the temperature of the two-step calcination is 550-850°C, for example, 550°C, 600°C, 700°C, 800°C or 850°C.
[0070] In one embodiment, the two-step calcination time is 6 to 18 hours, for example: 6 hours, 8 hours, 10 hours, 15 hours or 18 hours.
[0071] In a fourth aspect, the present disclosure provides a lithium-ion battery, wherein the lithium-ion battery comprises the composite lithium iron phosphate positive electrode material as described in the third aspect.
[0072] Compared with the prior art, the present invention has the following beneficial effects:
[0073] (1) The present invention first introduces tin dioxide with a hollow nanofiber structure, irradiates the tin dioxide with ultraviolet light to generate free radicals with strong oxidizing ability on its surface, oxidizes divalent iron into trivalent iron, and adjusts the pH to co-precipitate to form a tin dioxide composite iron phosphate material. At the same time, the introduction of tin dioxide helps to improve the electrical performance of lithium batteries.
[0074] (2) The battery made of the tin dioxide composite iron phosphate disclosed in the present invention has a 0.1C discharge capacity of more than 157.5 mAh / g, a 1C discharge capacity of more than 146.5 mAh / g, a discharge capacity of more than 143.7 mAh / g after 100 1C cycles, and a cycle retention rate of more than 98.1% after 100 1C cycles.
[0075] Other aspects will be apparent upon reading and understanding the drawings and detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] The accompanying drawings are used to provide further understanding of the technical solution of this article and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of this article and do not constitute a limitation on the technical solution of this article.
[0077] Figure 1 This is a SEM image of the composite iron phosphate material obtained in Example 1 of the present disclosure. DETAILED DESCRIPTION
[0078] The technical solution of the present disclosure is further described below through specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present disclosure and should not be regarded as specific limitations of the present disclosure.
[0079] Example 1
[0080] This embodiment provides a composite lithium iron phosphate positive electrode material, and the preparation method is as follows:
[0081] (1) Add polyvinyl pyrrolidone (PVP) to a mixed solvent of ethanol and DMF in a mass ratio of 1:1, the mass concentration of PVP is 10wt%, and then add SnCl4 to the mixed solution, the mass ratio of stannous chloride and PVP is 1:1, and heat and stir the mixed solution at 65°C for 30h to obtain a uniformly mixed spinning solution, and prepare tin dioxide nanofibers by electrospinning, the voltage is 14kV, the distance between the collecting plate and the needle is 18cm, and the spinning rate is 1mL / h. The tin dioxide fibers obtained by electrospinning are calcined in an air atmosphere, heated to 550°C at 3°C / min and kept warm for 3h, and cooled naturally to obtain tin dioxide with a hollow nanofiber structure;
[0082] (2) Disperse the hollow nanofiber tin dioxide, ferrous sulfate and ammonium dihydrogen phosphate in deionized water at a molar ratio of 0.05:1:1, mix them evenly at a speed of 1200 rpm, and irradiate them with ultraviolet light for 1.5 hours. At the same time, slowly add 25% ammonia water to adjust the solution to pH = 1.6 to produce precipitation, stir and heat to 75°C for aging for 6 hours, filter out the precipitate, and wash it with deionized water 3 times. Place the washed precipitate in a vacuum drying oven and dry it at 85°C for 6 hours, place it in a muffle furnace, heat it to 600°C at a rate of 4°C / min and keep it warm for 8 hours to obtain composite iron phosphate. The SEM image of the composite iron phosphate material is as follows Figure 1 shown.
[0083] (4) The composite iron phosphate and lithium carbonate are uniformly dispersed in water according to a stoichiometric ratio of iron to lithium of 1:1.02, 10 wt% of starch mixture is added, ball milled at a speed of 3500 rpm for 5 h until the mixture is uniformly mixed, and then spray dried to obtain a precursor powder. The precursor powder is kept at 400° C. for 1.5 h at a heating rate of 5° C. / min under a nitrogen atmosphere, and then heated to 750° C. and calcined at a high temperature for 9 h to obtain the composite lithium iron phosphate positive electrode material.
[0084] Example 2
[0085] This embodiment provides a composite lithium iron phosphate positive electrode material, and the preparation method is as follows:
[0086] (1) Add polyacrylonitrile to a mixed solvent of ethanol and DMF in a mass ratio of 2:1, the mass concentration of PVP is 10wt%, and then add SnCl4 to the mixed solution, the mass ratio of SnCl4 to PVP is 0.95:1, and the mixed solution is heated and stirred at 50°C for 48h to obtain a uniformly mixed spinning solution, and tin dioxide nanofibers are prepared by electrospinning, the voltage is 10kV, the distance between the collecting plate and the needle is 12cm, and the spinning rate is 2mL / h. The tin dioxide fibers obtained by electrospinning are calcined in an air atmosphere, heated to 600°C at 3°C / min and kept warm for 4h, and then naturally cooled to obtain tin dioxide with a hollow nanofiber structure;
[0087] (2) The hollow nanofiber tin dioxide, ferrous sulfate and phosphoric acid were dispersed in deionized water at a molar ratio of 0.03:0.98:1, mixed evenly at a speed of 1200 rpm, and irradiated with ultraviolet light for 1 hour. At the same time, 25% ammonia water was slowly added to adjust the solution to pH = 2.2 to produce precipitation, stirred and heated to 65°C for aging for 12 hours, filtered out the precipitate, and washed with deionized water 4 times. The washed precipitate was placed in a vacuum drying oven at 95°C for 6 hours, placed in a muffle furnace, heated to 500°C at a rate of 4°C / min and kept warm for 8 hours to obtain composite iron phosphate.
[0088] (4) The composite iron phosphate and lithium carbonate are uniformly dispersed in water according to a stoichiometric ratio of iron to lithium of 1:1.02, 3 wt% glucose is added, ball milling is performed at a speed of 3500 rpm for 5 h until the mixture is uniformly mixed, and then spray drying is performed to obtain a precursor powder. The precursor powder is kept at 400° C. for 2 h at a heating rate of 5° C. / min under a nitrogen protective atmosphere, and then the temperature is raised to 550° C. and calcined at a high temperature for 18 h to obtain the composite lithium iron phosphate positive electrode material.
[0089] Example 3
[0090] This embodiment provides a composite lithium iron phosphate positive electrode material, and the preparation method is as follows:
[0091] (1) Add polyvinyl pyrrolidone (PVP) to a mixed solvent of ethanol and DMF in a mass ratio of 3:1, the mass concentration of PVP is 10wt%, and then add SnCl4 to the mixed solution, the mass ratio of SnCl4 to PVP is 1.05:1, and heat the mixed solution at 70°C and stir for 12h to obtain a uniformly mixed spinning solution, and prepare tin dioxide nanofibers by electrospinning, the voltage is 18kV, the distance between the collecting plate and the needle is 25cm, and the spinning rate is 0.1mL / h. The tin dioxide fibers obtained by electrospinning are calcined in an air atmosphere, heated to 650°C at 3°C / min and kept warm for 3h, and then naturally cooled to obtain tin dioxide with a hollow nanofiber structure;
[0092] (2) The hollow nanofiber tin dioxide, ferrous sulfate and phosphoric acid were dispersed in deionized water at a molar ratio of 0.1:1:1, mixed evenly at a speed of 1200 rpm, and then irradiated with ultraviolet light for 3 hours. At the same time, 25% ammonia water was slowly added to adjust the solution to pH = 1.8 to produce precipitation, stirred and heated to 95°C for aging for 3 hours, filtered out the precipitate, and washed with deionized water 5 times. The washed precipitate was placed in a vacuum drying oven at 95°C for 6 hours, placed in a muffle furnace, heated to 700°C at a rate of 4°C / min and kept warm for 4 hours to obtain composite iron phosphate.
[0093] (4) The composite iron phosphate and lithium carbonate are uniformly dispersed in water according to a stoichiometric ratio of iron to lithium molar ratio of 1:1.02, 15 wt% glucose is added, ball milling is performed at a speed of 3500 rpm for 5 h until the mixture is uniformly mixed, and then spray drying is performed to obtain a precursor powder. The precursor powder is kept at 500° C. for 0.5 h at a heating rate of 5° C. / min under a nitrogen protective atmosphere, and then the temperature is raised to 850° C. and calcined at high temperature for 6 h to obtain the composite lithium iron phosphate positive electrode material.
[0094] Example 4
[0095] The only difference between this embodiment and embodiment 1 is that the molar ratio of the tin element in the hollow nanofiber tin dioxide to the iron element in the ferrous source is 0.01:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0096] Example 5
[0097] The only difference between this embodiment and embodiment 1 is that the molar ratio of the tin element in the hollow nanofiber tin dioxide to the iron element in the ferrous source is 0.2:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0098] Example 6
[0099] The only difference between this embodiment and embodiment 1 is that the illumination time is 0.5 h, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0100] Example 7
[0101] The only difference between this embodiment and embodiment 1 is that the calcination temperature after light irradiation is 400° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0102] Example 8
[0103] The only difference between this embodiment and embodiment 1 is that the calcination temperature after light irradiation is 800° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0104] Comparative Example 1
[0105] The only difference between this comparative example and Example 1 is that step (1) is not performed, tin dioxide is used directly, and other conditions and parameters are exactly the same as those in Example 1. A small amount of solution is taken out before and after irradiation with light and KSCN is added dropwise to check the existence form of iron ions.
[0106] Performance Test:
[0107] The lithium iron phosphate positive electrode materials obtained in the above embodiments and comparative examples are assembled into button-type lithium ion batteries for electrochemical performance testing. The specific steps are: the positive electrode material active substance, the conductive agent acetylene black and the adhesive polyvinylidene fluoride are uniformly mixed in N-methylpyrrolidone at a ratio of 90:5:5, and then coated on aluminum foil and placed in a vacuum drying oven for drying. After drying, the battery is assembled in an argon glove box and pressed into a positive electrode sheet with a tablet press. The negative electrode is a metal lithium sheet, the electrolyte is 1M LiPF6-EC:DMC (volume ratio 1:1), and a polypropylene porous membrane is used as a diaphragm. The charge and discharge voltage is controlled between 2.5-4.5V to test its electrochemical performance. The test results are shown in Table 1:
[0108] Table 1
[0109]
[0110] As can be seen from Table 1, from Examples 1-3, the 0.1C discharge capacity of the battery made from the tin dioxide composite iron phosphate disclosed in the present invention can reach more than 157.5 mAh / g, the 1C discharge capacity can reach more than 146.5 mAh / g, the discharge capacity after 100 cycles at 1C can reach more than 143.7 mAh / g, and the cycle retention rate after 100 cycles at 1C can reach more than 98.1%.
[0111] By comparing Example 1 with Examples 4-5, it can be seen that during the preparation process of the composite lithium iron phosphate positive electrode material disclosed in the present invention, the amount of tin added will affect its performance. The molar ratio of the tin element in tin dioxide to the iron element in the ferrous source is controlled at (0.03-0.1):1, and the composite lithium iron phosphate with better performance is obtained. If the amount of tin added is too large, the proportion in the iron phosphate is too high, and then it also occupies a non-negligible part in the subsequent synthesis of lithium iron phosphate, affecting the proportion of active substances in the positive electrode material; if the amount of tin added is too small, the oxidation of divalent iron is incomplete, and trivalent iron and divalent iron coexist in the solution. When generating iron phosphate, the divalent iron will be brought into the iron phosphate and co-precipitated together. The obtained iron phosphate contains impurity ions, which affects the material performance and has not fully utilized the iron source.
[0112] By comparing Example 1 with Example 6, and by comparing Example 1 with Examples 4-5, it can be seen that during the preparation process of the composite lithium iron phosphate positive electrode material disclosed in the present invention, the illumination time will affect its performance. When the illumination time is controlled within 1 to 3 hours, the composite lithium iron phosphate has better performance. If the illumination time is too short, sufficient free radicals cannot be generated, which will lead to incomplete oxidation of divalent iron.
[0113] By comparing Example 1 with Examples 7-8, it can be seen that in the preparation process of the composite lithium iron phosphate positive electrode material disclosed in the present invention, the temperature of calcination after illumination will affect its performance. The temperature of calcination after illumination is controlled at 500-750°C, and the composite lithium iron phosphate has better performance. If the temperature of calcination after illumination is too high, tin dioxide will affect the lattice characteristics of iron phosphate. If the temperature of calcination after illumination is too low, tin dioxide and iron phosphate will not be well composited, the dehydration of iron phosphate is incomplete, and some impurities have not been completely removed.
[0114] By comparing Example 1 and Comparative Example 1, it can be seen that the present disclosure prepares hollow nanofiber tin oxide through electrospinning technology. Since the hollow structure has a relatively large surface free energy, it can adsorb ions and attach to its surface. As a seed, it can accelerate the precipitation of primary particles of iron phosphate. Before and after illumination, KSCN was added to the solution dropwise. It was found that there was no change in the solution before illumination. After illumination, red flocculent complexes were produced by adding KSCN to the sampled solution. This is due to the presence of trivalent iron ions. This comparison shows that the present disclosure uses illumination, and tin dioxide is used as a photocatalyst to stimulate the separation of electron-hole pairs under illumination, forming hydroxyl radicals (·OH) and superoxide radicals (·O2 - ), directly oxidizes the divalent iron into trivalent iron without adding any additional oxidant, and forms a composite of tin dioxide / ferric phosphate.
Claims
1. A method for preparing a composite ferric phosphate, comprising the following steps: (1) mixing a tin source and a template agent with a first solvent, heating and stirring to obtain a spinning solution, and sintering after electrospinning to obtain hollow nanofiber tin dioxide; (2) mixing the hollow nanofiber tin dioxide, ferrous source and phosphorus source with a second solvent, treating with light while adjusting the pH, aging and calcining to obtain the composite iron phosphate; The receiving distance of the electrospinning treatment in step (1) is 12 to 25 cm, the voltage of the electrospinning treatment is 10 to 18 kV, the rate of the electrospinning treatment is 0.1 to 2 mL / h, the heating rate of the sintering is 0.5 to 3 ° C / min, the sintering temperature is 550 to 650 ° C, the sintering time is 3 to 5 hours, the mass ratio of the tin source and the template agent is (0.95 to 1.05): 1, the molar ratio of the tin element in the hollow nanofiber tin dioxide, the iron element in the ferrous source and the phosphorus element in the phosphorus source in step (2) is (0.03 to 0.1): (0.98 to 1): 1, the light source of the illumination includes ultraviolet light, the illumination time is 1 to 3 hours, and the calcination temperature is 500 to 750 ° C.
2. The preparation method according to claim 1, wherein The first solvent includes ethanol and DMF.
3. The preparation method according to claim 2, wherein The mass ratio of the ethanol to DMF is (1-3):
1.
4. The preparation method according to claim 1, wherein The temperature of the heating and stirring is 50-70°C.
5. The preparation method according to claim 1, wherein The heating and stirring time is 12 to 48 hours.
6. The preparation method according to claim 1, wherein The second solvent includes deionized water.
7. The preparation method according to claim 1, wherein The method of adjusting the pH in step (2) includes adding an alkaline substance.
8. The preparation method according to claim 1, wherein The pH is 1.4 to 2.
2.
9. The preparation method according to claim 1, wherein The aging temperature in step (2) is 65-95°C.
10. The preparation method according to claim 1, wherein The aging time is 3 to 12 hours.
11. The preparation method according to claim 1, wherein The calcination time is 4 to 8 hours.
12. A composite iron phosphate obtained by the method according to any one of claims 1 to 11. 13 . A composite lithium iron phosphate positive electrode material, wherein the composite lithium iron phosphate positive electrode material is prepared by mixing the composite iron phosphate according to claim 12 with a lithium source and a carbon source and calcining the mixture.
14. The composite lithium iron phosphate positive electrode material according to claim 13, wherein: The calcination includes one-step calcination and two-step calcination.
15. The composite lithium iron phosphate positive electrode material according to claim 14, wherein: The temperature of the one-step calcination is 400-500°C.
16. The composite lithium iron phosphate positive electrode material according to claim 14, wherein: The time of the one-step calcination is 0.5 to 2 hours.
17. The composite lithium iron phosphate positive electrode material according to claim 14, wherein: The temperature of the second step calcination is 550-850°C.
18. The composite lithium iron phosphate positive electrode material according to claim 14, wherein: The time of the two-step calcination is 6 to 18 hours.
19. A lithium ion battery comprising the composite lithium iron phosphate positive electrode material according to any one of claims 14 to 18.
Citation Information
Patent Citations
Battery-grade anhydrous ferric phosphate and preparation method thereof
CN109305663A
Lithium iron phosphate nanofiber as lithium ion battery cathode material and preparation method thereof
CN102340002A
Composite positive electrode of lithium ion battery as well as preparation method and application to all-solid-state battery thereof
CN103956458A